Rate dependent fracture behavior of highly cross-linked epoxy resin. (October 2022) - Mishra, K.; Brassart, L.; Singh, A.
Graphical abstract: Highlights: Fracture toughness of epoxy decreases with crack-tip strain rate when they are low. Fracture toughness of epoxy saturates for crack tip strain rate higher that 0.02 s −1 . Crazing is the dominant fracture micro-mechanism in epoxy when sharp cracks are present. Disentanglement crazing is dominant at low strain rate. Scission crazing is dominant at high strain rate. Abstract: The fracture behavior of highly cross-linked epoxy resin under plane strain conditions for crack tip strain rates spanning over four orders of magnitude (10 -4 −10 -1 s −1 ) has been examined. The plane strain fracture toughness initially decreases with increasing crack tip strain rate ( ∊ ̇ t i p ) and saturates at ∼ 0.8 MPa-m −0.5 after ∊ ̇ t i p ∼ 0.02 s −1 is attained. For all the fracture specimens, a fracture process zone (FPZ) forms ahead of the sharp pre-crack prior to catastrophic failure due to the intensified stresses ahead of the crack tip. This FPZ region consists of crazes that govern the micro mechanism of fracture and this was explicitly proved using in-situ testing in a scanning electron microscope. For low strain rates, crazing in the FPZ is expected to be dominated by chain disentanglements, with craze openings more than 200 nm, whereas, chain-scission is expected to dominate at higher strain rates, with lower craze openings of ∼ 150 nm.